The Concept of Educator in Islam (The interpretation of Q.S. Ali-Imran Verses 133-136 according to Ibn Kathir) - Sardani, Sardani; Nahar, Syamsu; Zulheddi, Zulheddi (TARBAWY: Indonesian Journal of Islamic Education, 2024)
This study aims to describe the contents of the Al-Qur’an surah Ali Imran verses 133-136 and analyze the character of educators contained in the Al-Qur’an sura Ali Imran verses 133-136. This research is included in library research. The results of this study are: that there are educator characters contained in surah Ali Imran verses 133-136, such as: concern for the hereafter, piety to Allah, simplicity in doing good, humility, awareness of mistakes, willingness to improve oneself, unity, work together, and appreciating God’s grace. This approach helps form educators who are responsible and care about the formation of student character, namely: a) Forming a good personality for them and improving students continuously by always rushing in goodness. b) Rewards in the form of heaven for educators to strengthen the faith of students. c) Doing good must be made a habit